Quantitative genetic variation for resistance to the parasite Ichthyophthirius multifiliis in the Neotropical fish tambaqui (Colossoma macropomum) - Lira, Lieschen V.G. [UNESP]; Ariede, Raquel B. [UNESP]; Freitas, Milena V. [UNESP]; Mastrochirico-Filho, Vito A. [UNESP]; Agudelo, John F.G. [UNESP]; Barría, Agustin; Yáñez, José M.; Hashimoto, Diogo T. [UNESP] (Elsevier, 2020)
Tambaqui (Colossoma macropomum) is the main native fish produced in continental aquaculture from South America. However, its production has been negatively affected by significant economic losses due to frequent outbreaks caused by the parasite Ichthyophthirius multifiliis. Genetic selection for I. multifiliis resistance may represent a sustainable and effective alternative to reduce mortality and, therefore, improve production of tambaqui. The estimation of genetic parameters is needed to validate whether I. multifiliis resistance can be included in genetic improvement programs. The aim of this study was to estimate variance components and heritability for I. multifiliis resistance in tambaqui, through experimental challenge of 218 individuals from eight full-sib families. Survival status (SS), time of death (TD) and parasite load (PL) of fish presenting clinical signs of I. multifiliis infestation were recorded in the cohabitation experimental challenge. The total cumulative survival rate varied significantly among families (16 to 100%) and TD ranged from 217 to 254 hours post cohabitation, which indicates the presence of significant phenotypic variation related to resistance to I. multifiliis infestation. High values for heritability were estimated for SS and TD (0.46 ± 0.09 and 0.60 ± 0.18, respectively). However, differences among families and heritability value were not significant for PL. This study represents the first report on genetic parameters for disease resistance against the parasite I. multifiliis in a Neotropical fish species. The results presented here suggest that resistance to I. multifiliis in tambaqui can be improved through selective breeding.
Keywords: animal breeding; breeding program; disease resistance; heritability